Increasing incidence of malignant mesothelioma after exposure to asbestos during home maintenance and renovation - Olsen, N.; Franklin, P.; Reid, Alison; de Klerk, N.; Threlfall, T.; Shilkin, K.; Musk, B. (2011)
Objective: To determine trends in incidence of malignant mesothelioma (MM) caused by exposure to asbestos during home maintenance and renovation. Design, setting and participants: Using the Western Australian Mesothelioma Register, we reviewed all cases of MM diagnosed in WA from 1960 to the end of 2008, and determined the primary source of exposure to asbestos. Categories of exposure were collapsed into seven groups: asbestos miners and millers from Wittenoom; all other asbestos workers; residents from Wittenoom; home maintenance/renovators; other people exposed but not through their occupation; and people with unknown asbestos exposure; or no known asbestos exposure. Latency periods and age at diagnosis for each group were calculated and compared. Results: In WA, 1631 people (1408 men, 223 women) were diagnosed with MM between 1960 and 2008. Since 1981, there have been 87 cases (55 in men) of MM attributed to asbestos exposure during home maintenance and renovation, and an increasing trend in such cases, in both men and women. In the last 4 years of the study (2005-2008), home renovators accounted for 8.4% of all men and 35.7% of all women diagnosed with MM. After controlling for sex and both year and age at diagnosis, the latency period for people exposed to asbestos during home renovation was significantly shorter than that for all other exposure groups, but the shorter follow-up and difficulty recalling when exposure first occurred in this group may partly explain this. Conclusions: MM after exposure to asbestos during home renovation is an increasing problem in WA, and these cases seem to have a shorter latency period than other types of exposure. MM cases related to renovation will probably continue to increase because of the many homes that have contained, and still contain, asbestos building products.